Back Cover: Chemical Preparation of Graphene Materials Results in Extensive Unintentional Doping with Heteroatoms and Metals (Chem. Eur. J. 48/2014). Issue 48 (24th November 2014) - Chua, Chun Kiang; Ambrosi, Adriano; Sofer, Zdeněk; Macková, Anna; Havránek, Vladimír; Tomandl, Ivo; Pumera, Martin
<x xml:space="preserve">Abstract</x> Contamination of graphene materials with heteroatoms and metals is inevitable with successive chemical treatments. Typical oxidation and reduction procedures of graphite and graphene oxide, respectively, result in unintentional introduction of heteroatoms (N, B, Cl, S) or metals (Mn, Al) of up to 3 at %. Despite the contamination level being comparable to intentionally doped graphene materials, such unintentional introduction of heteroatoms or metals is seldom demonstrated. Therefore, the grey area between "contamination" and "doping" processes could be expanding. Prudent characterizations of graphene materials are thus advocated to avoid misplaced judgments on their electronic and electrochemical properties. For more details, see the Full Paper by M. Pumera et al. on page 15760 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>